Infrared precipitation on climate hazards using rainfall dataset over inter-tropical convergence zone - A. Purwandani; Supari ,; W. Ambarwulan; U. Haryoko; I.P. Dewi; Y. Anantasena; Y.S. Djajadihardja; H. Sadmono; S.I. Sachoemar; D. Nugroho (Global Journal of Environmental Science and Management, 2025)
BACKGROUND AND OBJECTIVES: Hydrometeorological disaster management and agriculture sectors require accurate spatial and temporal rainfall data. However, in situ rainfall gauges were very limited and distributed unevenly. In this context, satellite-based rainfall estimates were used as a reference and complement to in situ measurements on Kalimantan Island, Indonesia. The island possessed complex climate phenomena such as the inter-tropical convergence zone. This study aimed to i) validate rainfall data estimates from climate hazards group infrared precipitation with stations, ii) identify movement in Inter-Tropical Convergence Zone variability, and iii) analyze the variability of rainfall in the inter-tropical convergence zone region.METHODS: A synthesis of descriptive and categorical statistics was used, with European Centre for Medium-Range Weather Forecasts Reanalysis 5th generation data serving as the basis for identifying the inter-tropical convergence zone, while power spectrum density analysis was used to assess rainfall variability. The normal characteristics of monthly rainfall in each season type are compared between observed rainfall data, climate hazards group infrared precipitation with stations with correction, and climate hazards group infrared precipitation with stations without correction.FINDINGS: The results showed that the best Climate Hazards Group InfraRed Precipitation with Stations performance was found in the southeast of Kalimantan, characterized by flat to undulating areas from the coast to the valley behind the hills, mainly forest and cultivated land cover types, and a high density of rainfall observations. The climate hazards group infrared precipitation with stations performance testing approach from point to pixel versus using the Seasonal Zone region is similar; however, point to pixel is clearly preferable. The movement pattern of the intertropical convergence zone influences the accuracy of rainfall estimation using climate hazards group infrared precipitation with stations. The climate hazards group''s infrared precipitation dataset with stations that have been validated against the movement of the intertropical convergence zone in Kalimantan. Seasonal zones with equatorial, monsoonal, equatorial-1, equatorial-2, Monsoonal-1, and Monsoonal-2 types generally does not affect the performance differences of the climate hazards group infrared precipitation with stations. The variation between climate hazards group infrared precipitation with stations rainfall estimates and observations does not differ systematically.CONCLUSION: Climate hazards group infrared precipitation with stations performance was strongly influenced by Inter-Tropical Convergence Zone movements, and the dataset was reliable in estimating rainfall for areas in Kalimantan with a reduced number of observation stations. The inter-tropical convergence zone movement pattern is impacted by local, regional, and global climate variability caused by land-sea-atmosphere interactions on the Indonesian maritime continent, resulting in significant variations in the center and width of the inter-tropical convergence zone band. the major cycle of corrected and observed climate hazards group infrared precipitation with stations rainfall in the seasonal zone is annual and seasonal, with monsoonal and equatorial rainfall types.